High Speed and Low Pedestal Error Bootstrapped CMOS Sample and Hold Circuit - Agung Setiabudi; Hiroki Tamura; Koichi Tanno (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A new high speed, low pedestal error bootstrapped CMOS sample and hold (S/H) circuit is proposed for high speed analog-to-digital converter (ADC). The proposed circuit is made up of CMOS transmission gate (TG) switch and two new bootstrap circuits for each transistor in TG switch. Both TG switch and bootstrap circuits are used to decrease channel charge injection and on-resistance input signal dependency. In result, distortion can be reduced. The decrease of channel charge injection input signal dependency also makes the minimizing of pedestal error by adjusting the width of NMOS and PMOS of TG switch possible. The performance of the proposed circuit was evaluated using HSPICE 0.18-m CMOS process. For 50 MHz sinusoidal 1 V peak-to-peak differential input signal with a 1 GHz sampling clock, the proposed circuit achieves 2.75 mV maximum pedestal error, 0.542 mW power consumption, 90.87 dB SNR, 73.50 SINAD which is equal to 11.92 bits ENOB, -73.58 dB THD, and 73.95 dB SFDR.